APPLICATION OF CERTAINTY FACTOR METHOD TO DIAGNOSING RABIES IN PETS - Nadia Astri Wulandari; Suci Andriyani (JURNAL TEKNISI, 2025)
Abstract: Rabies is an infectious disease caused by the Lyssavirus virus from the Rhabdoviridae family. This disease is spread through the bite of animals such as dogs and cats, which are widely kept by the community. Lack of information about rabies causes its spread to be increasingly widespread. Therefore, an expert system is needed that can help early diagnosis of this disease. This study aims to develop an expert system based on the Certainty Factor (CF) method in diagnosing rabies in pets. Rabies symptom data were collected and calculated using the CF algorithm to determine the level of certainty of the diagnosis. The results showed that the expert system was able to diagnose rabies with high accuracy. Of the 100 samples tested, 90% showed symptoms of the prodromal stage, which is the early phase of infection. This system also provides prevention recommendations for pet owners. In conclusion, an expert system based on Certainty Factor can help early detection of rabies and provide useful information for pet owners in taking preventive measures.Keywords: rabies; certainty factor; expert system; disease diagnose.Â Abtrak: Rabies adalah penyakit menular yang disebabkan oleh virus Lyssavirus dari keluarga Rhabdoviridae. Penyakit ini menyebar melalui gigitan hewan seperti anjing dan kucing, yang banyak dipelihara oleh masyarakat. Kurangnya informasi mengenai rabies menyebabkan penyebarannya semakin luas. Oleh karena itu, diperlukan sistem pakar yang dapat membantu diagnosis dini penyakit ini. Penelitian ini bertujuan untuk mengembangkan sistem pakar berbasis metode Certainty Factor (CF) dalam mendiagnosis rabies pada hewan peliharaan. Data gejala rabies dikumpulkan dan dihitung menggunakan algoritma CF untuk menentukan tingkat kepastian diagnosis. Hasil penelitian menunjukkan bahwa sistem pakar mampu mendiagnosis rabies dengan akurasi tinggi. Dari 100 sampel yang diuji, 90% menunjukkan gejala tahap prodromal, yaitu fase awal infeksi. Sistem ini juga memberikan rekomendasi pencegahan bagi pemilik hewan. Kesimpulannya, sistem pakar berbasis Certainty Factor dapat membantu deteksi dini rabies serta memberikan informasi yang berguna bagi pemilik hewan dalam mengambil tindakan pencegahan.Kata kunci: rabies; certainty factor; sistem pakar; diagnosis penyakit.